Evaluasi dan Rekomendasi Geoteknik pada Lereng Produksi Penambangan Andesit PT Mitra Multi Sejahtera di Kecamatan Cikalong Kulon, Kabupaten Cianjur, Provinsi Jawa Barat - Nirmaya Wulandari; Iswandaru; Elfida Moralista (Bandung Conference Series: Mining Engineering, 2022)
Abstract. PT Mitra Multi Sejahtera is a company engaged in the mining sector with andesite commodities. The slope of the company has a steep slope and a large number of discontinuous fields that have the potential to make the slope unstable. This research was conducted to determine the potential types of landslides, actual and optimal slopes, safety factors and probability of failure, slope stability, and slope geometry recommendation. This research uses a methodology in the form of Q-Slope analysis, limit equilibrium method, and probabilistic method on 2 slope segments. Q-Slope analysis observes the physical properties of the discontinuous plane to obtain the optimal slope. Limit equilibrium and probabilistic methods were studied using inputs of physical and mechanical properties in the form of natural density, cohesion, and friction angle which were analyzed through Monte Carlo simulation to obtain the value of the safety factor and probability of failure. The slope of segment 1 has an actual slope of 80o and an optimal slope of 83o with a safety factor of 7.233. The slope of segment 2 has an actual slope of 76o and an optimal slope of 88o with a safety factor of 7.095. The probability of failure generated from the two slope segments is 0.7% in dynamic conditions. The results of data analysis show that the slopes are in a safe and stable condition. The recommended slope geometry recommendation is to make an overall slope with a height of 40 meters and an overall slope of 57o by dividing it into 4 benches. Abstrak. PT Mitra Multi Sejahtera merupakan suatu perusahaan yang bergerak pada bidang pertambangan dengan komoditas andesit. Lereng pada perusahaan tersebut memiliki kemiringan yang curam dan bidang diskontinu dalam jumlah yang cukup banyak sehingga berpotensi membuat lereng menjadi tidak stabil. Penelitian ini dilakukan untuk mengetahui potensi jenis longsoran, kemiringan lereng aktual dan optimal, faktor keamanan dan probabilitas longsor, kestabilan lereng, serta rekomendasi geometri lereng.Penelitian ini menggunakan metodologi berupa analisis Q-Slope, metode kesetimbangan batas, dan metode probabilistik pada 2 segmen lereng. Analisis Q-Slope mengamati sifat fisik bidang diskontinu hingga mendapatkan kemiringan lereng optimal. Metode kesetimbangan batas dan probabilistik dikaji menggunakan input sifat fisik dan mekanik berupa bobot isi natural, kohesi, dan sudut gesek dalam yang dianalisis melalui simulasi monte carlo untuk mendapatkan nilai faktor keamanan dan probabilitas longsor. Lereng segmen 1 memiliki kemiringan aktual 80o dan kemiringan optimal 83o dengan nilai faktor keamanan sebesar 7,233. Lereng segmen 2 memiliki kemiringan aktual 76o dan kemiringan optimal 88o dengan nilai faktor keamanan sebesar 7,095. Probabilitas longsor yang dihasilkan dari kedua segmen lereng sebesar 0,7% dalam keadaan dinamis. Hasil analisis data menunjukkan bahwa lereng dalam kondisi yang aman dan stabil. Rekomendasi geometri lereng yang disarankan yakni membuat lereng keseluruhan dengan tinggi 40 meter dan overall slope 57o dengan membaginya ke dalam 4 jenjang.